Contrastive Analysis Between Lio Language And English (A Phonological View) - Erlina Intantiana Eka; Rikardus Nasa; Yanto Yanto (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This ressearch discusses the comparison of two languages, namely Lio and English, with Lio as the regional language or language of origin and English as the target language. In this study limited the study to comparing how many vowels and consonants there are from each language, after researchers know the number of vowels and consonants present in Lio language researchers compare with vowels and consonants in English to find out where the similarities and differences between vowel phonemes and consonant phonemes from the two languages are located. In this study the author used a qualitative descriptive method with the aim of knowing the phonemes of vowels and consonants in Lio and English, then from the phonemes of vowels and consonants the author compared to find out the location of similarities and differences between the two languages, with the data collection technique used was to conduct interviews with local communities and the results of the interviews were recorded and analyzed by the author. From this study it can be seen that:: (1). There are 5 types of vowels, namely; a, I, u, e, o in Lio and English, (2) there are 20 types of consonants in Lio b, c, d, f, g, h, j, k, l, m, n, p, r, s,t,w and 24 consonants in English, namely; B,C,D,F,G,H,J,K,L,M,N,P,Q,R,S,T,V,W,X,Y,Z. (3) The difference between the two languages lies in the sound of speech and consonants. Different consonants are: consonants q, y, z, x, which exist in Lio besides that there are changes in pronunciation sounds in English vowels and consonants while in Lio language there can be no sound changes in both vowels and consonants. (4) The similarities between the two languages are vowels of both languages and some consonants4.